Characteristics of Social Work With Youth in the United Kingdom (Inclusive Aspects) - Lytovchenko, Oleksandr (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The materials of this article present the results of a study on the characteristics of social work with youth in the United Kingdom, focusing on inclusive aspects and considering the cultural and historical specifics of England, Scotland, Northern Ireland, and Wales. The research methodology involved an analysis of British and Ukrainian sources on social work, materials from official portals of international organizations, regulatory documents, and analytical reports on social work with youth from England, Scotland, Northern Ireland, and Wales, as well as the generalization and systematization of data. The article actualizes the concepts of inclusion and exclusion within the context of social work. It is emphasized that, for social work with youth in the United Kingdom, creating equal opportunities, ensuring accessibility, fostering involvement, and counteracting discrimination are crucial. Significant attention is paid to supporting vulnerable groups of young people who need to integrate into British society. The characteristics of social work with youth in the United Kingdom (inclusive aspects) are examined, taking into account the cultural, historical, and religious specifics of England, Scotland, Northern Ireland, and Wales. The paper presents distinctions stemming from these cultural and historical specifics, such as the emphasis on supporting youth from different ethnic groups and linguistic communities, particularly the Welsh-speaking community (Wales), and the implementation of educational, cultural, and social programs to overcome historical barriers and the consequences of political and religious division between Protestants and Catholics (Northern Ireland). It is concluded that while social work with youth differs somewhat across the four countries of the United Kingdom, the issue of inclusion is essential and relevant for all of them. Based on an analysis of empirical data from a survey of British youth (from the comprehensive report “Next Generation 2024”), a conclusion is drawn about the significant attention given to the integration of vulnerable groups of British youth. This is particularly evident in young people's optimistic perceptions of their own future, as noted by 65% of respondents. This article does not claim to comprehensively cover all inclusive aspects of social work with youth in the United Kingdom. It focuses on the analysis of the cultural and historical specifics of England, Scotland, Northern Ireland, and Wales in this context.